Overexpression of the Liriodendron tulipifera TPS32 gene in tobacco enhances terpenoid compounds synthesis - Wu, Junpeng; Bu, Manli; Zong, Yaxian; Tu, Zhonghua; Cheng, Yanli; Li, Huogen (Frontiers in Plant Science, 2024)
Liriodendron, a relic genus from the Magnoliaceae family, comprises two species, L. tulipifera and L. chinense. L. tulipifera is distinguished by its extensive natural distribution in Eastern North America. Conversely, L. chinense is nearing endangerment due to its low regeneration rate. A pivotal aspect in the difference of these species involves terpenoids, which play crucial roles in plant growth and attracting pollinators. However, the complex molecular mechanisms underlying terpenoid roles in Liriodendron are not well understood. Terpene Synthases (TPS) genes are widely reported to play a role in terpenoid biosynthesis, hence, this study centers on TPS genes in Liriodendron spp. Employing multiple bioinformatics methods, a differential expression gene in L. tulipifera, LtuTPS32, was discerned for further functional analysis.Subcellular localization results reveal the involvement of LtuTPS32 in chloroplastassociated processes, hence participate in terpenoid biosynthesis within chloroplasts.Heterologous transformation of the LtuTPS32 gene into tobacco significantly elevates the levels of common terpenoid compounds, including chlorophyll, gibberellin, and carotenoids. Collectively, these findings not only underscore the role of the LtuTPS32 gene in the biosynthesis of terpenoids but also lay a foundation for future research on interspecific differences in Liriodendron.